Financial Health of Indonesian Islamic Banks: A CAMEL-Based Analysis During and After the COVID-19 Pandemic: Financial Health of Indonesian Islamic Banks: A CAMEL-Based Analysis During and After the COVID-19 Pandemic - EKo Albar Wahyudi; Nurul Qalbi Awaliyah; Asriyana; Nini Andriani; Habib MUhammad Shabib (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2026)
This study aims to analyze the financial health of Indonesian Islamic commercial banks during and after the COVID-19 pandemic using the CAMEL framework. Data from nine Islamic commercial banks in Indonesia for the 2020–2024 period were examined using a descriptive quantitative approach with CAR, KAP, NPM, ROA, BOPO, and FDR as financial health indicators. Results show that Islamic banks generally maintained strong capital adequacy and controlled asset quality, while profitability, operational efficiency, and liquidity varied across banks. The average CAMEL score improved from the fairly healthy category in 2020–2021 to the healthy category in 2022–2024. Bank Mega Syariah, Bank BTPN Syariah, and Bank NTB Syariah recorded the strongest financial health, whereas Bank Aladin Syariah and KB Bank Syariah still faced challenges in profitability and efficiency. These findings suggest that Islamic bank soundness is bank-specific and component-specific. Management and regulators should prioritize efficiency, earning capacity, and liquidity control beyond capital adequacy. This study is descriptive and does not test causal relationships among financial ratios